Urban Metabolism: From Molecular Scale to Anthropogenic Systems - Paul Hans Brunner (Jurnal Rekayasa Kimia & Lingkungan, 2025)
The aim of this paper is to show how an “Urban Metabolism” approach can be used for analysing, designing, and optimizing material and energy flows and stocks in human settlements. For this purpose, material flow analysis (MFA) and substance flow analysis (SFA) is applied in a rigid way to quantitatively model metabolic processes such as supply and disposal of goods in a city. The characteristics of relevant material flows and stocks of urban areas in space and time are examined. Results of two metabolic case studies on resources, waste management, and environmental protection are presented. By introducing the so called “Activity” concept, it is shown how the Urban Metabolism approach is instrumental for the design of sustainable anthropogenic systems. Finally, it is suggested to use the methodology for technology assessments and the optimization of entire anthropogenic systems.